Prostaglandin D2 modulates calcium signals induced by prostaglandin E2 in neurons of rat dorsal root ganglia. (15th June 2015) - Ott, Daniela; Simm, Björn; Pollatzek, Eric; Gerstberger, Rüdiger; Rummel, Christoph; Roth, Joachim
Highlights: A group of dorsal root ganglia (DRG) neurons is responsive to menthol and PGE2 . These neurons are putative cold-sensors. The strength of PGE2 -induced Ca 2+ -signals in DRG-neurons is modulated by PGD2 . Cold-sensors may participate in systemic responses during subcutaneous inflammation. Abstract: Fever in response to a localized subcutaneous stimulation with a low dose of lipopolysaccharide (LPS) can be attenuated by co-administration of a local anesthetic or the non-selective cyclooxygenase (COX) inhibitor diclofenac at doses, which do not exert systemic effects when injected at sites remote from the area of inflammatory stimulation. These results suggest a participation of neuronal afferent signals mediated by COX-products in the manifestation of fever under these conditions. We therefore, measured intracellular Ca 2+ -concentrations in cultured neurons from rat dorsal root ganglia (DRG) stimulated with the pyrogenic mediator prostaglandin E2 (PGE2 ), the anti-inflammatory and antipyretic mediator PGD2, mixtures of both PGs, and menthol using the fura-2 ratio imaging technique. Neurons could be grouped according to their size with diameters of about 15 μm (small), 35 μm (medium sized), or 55 μm (large). 96 out of 264 neurons responded to PGE2 with pronounced Ca 2+ -signals, 53 of them being also responsive to menthol, indicative of their function as cold-sensors. 80% of these neurons belonged to the medium sized group. In a next experiment, we tested whether Ca 2+ -signals of PGE2 responsive neurons were modulated by PGD2 . In 60% of all neurons investigated ( n = 57), the strength of the PGE2 -induced Ca 2+ -signals was reduced by co-administration of PGD2 . This effect was also observed in those neurons that were responsive to PGE2 and menthol ( n = 23; p < 0.001). This observation indicates antagonistic effects of PGE2 and PGD2 on a neuronal pathway that involves cold sensors and is activated during a localized subcutaneous inflammation. This finding might provide an explanation for the reported antipyretic and anti-inflammatory capacities of PGD2 .